PENGELOLAAN LABORATORIUM KOMPUTER - Arpan Supianto (UNIVERSITAS BENGKULU, 2016)
The purpose of this research is to describe the condition of computer laboratory management on, planning, organizing, actuating, evaluating and controlling. The subject of thisresearch was the principal, teachers, laboratory manager, technicians and students at the Vocational High School District 1 Putri Hijau North Bengkulu. This research used a descriptivequalitative method. The data collecting technique used interview, observation, and documentation, and analyze by reducing the data, presenting the data, and drawing conclusion. The results of this research can be concluded that the management of computer laboratory at this school was done well so far but needs to be improved especially in the anagement of both facilities and human resources.Keywords: computer laboratory, management